Optimization of temperature and extraction time for the nutritional and phytochemical contents of corn bran with ultrasonic-method - Haslina Haslina; Dewi Larasati; Ery Pratiwi; Novizar Nazir; Ika Fitriana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
One of the natural antioxidants sources that have the potential to be utilized as raw material for functional food is corn bran. Corn bran is a by-product of the milling process of corn that is gaining attention as a functional food is increasing in recent years. This study aimed to optimize temperature and extraction time for the nutritional and phytochemical contents of corn bran with ultrasonic-method. Optimized Custom Design was applied to investigate the effect of experimental factors on the nutritional and phytochemical contents. This study used Randomized Block Design (RBD) arranged in-factorial with 3 treatments, namely temperature and time of extraction. Temperature: A1=500C, A2=550C, A3=600C, and A4=650C, and time: B1=10 minutes, B2=15 minutes, B3=20 minutes, and B4=25 minutes. The data obtained were analyzed statistically using ANOVA with a significance level of 95% and then processed with Software DX13.0 ® program. The results of the research show the formula of the experiment which is optimal at a temperature of 500C and 10 minutes. In this condition, the result is the yield at 38.34%, nutritional contents (water at 9.17%; ash at 0.33%; fat at 1.33%, protein at 4.40%, carbohydrates at 85.47%; and crude fiber at 1.88%. produce yield 38.34%, and phytochemical contents (total phenols at 1778.07 µg GAE/g. flavonoids at 92.11 µg GAE/g, vitamin C at 5.84 mg, antioxidant activity at 43.33%, and tannins at 0.11%). This study implies that there is an increase in added value from the conversion of corn bran into nutrient-rich products and has a promising phytochemical content.